Bridging the Gap by Exploring Inequalities in Access to Land and Disparities in Agrarian Law in Indonesia - Natasya Aulia Putri; S. Sarmilah; Jennifer Velda; Wulan Mirdayanti Zschock (Faculty of Law, University of Jember, Indonesia, 2024)
This article explores the historical underpinnings of unequal access to land in Indonesia, tracing its roots to colonial legacies and the lasting impact of Dutch colonial rule. Through an examination of laws such as the 1870 Agrarian Law, it highlights how indigenous peoples were systematically dispossessed of their land, exacerbating social inequality and perpetuating economic injustice. It also underscores the widespread legal uncertainty faced by marginalized groups, which hinders their access to essential services and deepens social and economic disparities. After the proclamation, Indonesia chose to create new regulations by passing Law No. 5/1960 on the Basic Regulation of Agrarian Principles (UUPA). This law became the legal framework for Indonesia's agrarian reform. Furthermore, this article explores the critical role of agrarian reform in reducing this disparity, advocating for comprehensive policy reforms that aim to strengthen legal protections for the land rights of marginalized communities. By elucidating the historical trajectory of land access inequality and its contemporary manifestations, this article contributes to a better understanding of the complex socio-legal dynamics that shape land tenure in Indonesia. Through a critical examination of colonial legacies and current policy frameworks, it seeks to inform efforts aimed at promoting social justice and equitable resource distribution. Ultimately, the article underscores the importance of agrarian reform that prioritizes the rights and welfare of marginalized communities, hoping to pave the way towards a more inclusive land governance regime and sustainable development. KEYWORDS : Land Access, Inequality, Agrarian Law, Agrarian Reform